The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.3892/ijo.2011.1285
|View full text |Cite
|
Sign up to set email alerts
|

Emodin reverses gemcitabine resistance in pancreatic cancer cells via the mitochondrial apoptosis pathway in vitro

Abstract: Gemcitabine resistance is a common problem of pancreatic cancer chemotherapy, and how to reverse it plays an important role in the treatment of pancreatic cancer. This study investigated the effect of emodin on the gemcitabine-resistant pancreatic cancer cell line SW1990/Gem, and explored the potential mechanism of its action. SW1990/Gem was obtained by culture of the pancreatic cancer cell line SW1990 in vitro by intermittently increasing the concentration of gemcitabine in the culture medium for 10 months, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 37 publications
(41 reference statements)
3
31
0
Order By: Relevance
“…Emodin has also been shown to enhance the activity of gemcitabine-mediated pro-apoptosis in pancreatic cancer cells via Akt inhibition and NF-kappaB activation, thus promoting the mitochondria-dependent apoptotic pathway [42]. In the pancreatic cancer cell line SW1990E, emodin was found to induce apoptosis by significantly downregulating NF-kappaB DNA-binding activity, and survivin and MMP-9 expression in SW1990 cells [43][44][45]. Moreover, the expression of cleaved-caspase-3 was found to be upregulated in SW1990 cells after emodin treatment [15].…”
Section: Discussionmentioning
confidence: 98%
“…Emodin has also been shown to enhance the activity of gemcitabine-mediated pro-apoptosis in pancreatic cancer cells via Akt inhibition and NF-kappaB activation, thus promoting the mitochondria-dependent apoptotic pathway [42]. In the pancreatic cancer cell line SW1990E, emodin was found to induce apoptosis by significantly downregulating NF-kappaB DNA-binding activity, and survivin and MMP-9 expression in SW1990 cells [43][44][45]. Moreover, the expression of cleaved-caspase-3 was found to be upregulated in SW1990 cells after emodin treatment [15].…”
Section: Discussionmentioning
confidence: 98%
“…The administration of emodin in pregnant mice has been previously reported, which indicated its high safety [24]. Liu et al showed that emodin could be used as a sensitizer in the gemcitabine-resistant pancreatic cancer cells [25]. HL-60/ADR cells overexpressed multidrug resistance-associated protein (MRP1) are highly resistant to different chemotherapeutic agents [13,26].…”
Section: Discussionmentioning
confidence: 99%
“…Molecular mechanisms involved include tyrosine kinases [3,31], casein kinase II [1], protein kinase C [47], AKT/mTOR [1,28,62], NF-κB [1,67,68], HIF-1α [1], STAT3 [1,59], p53 [1,21,23,32,54], Wnt signaling [69], Bcl-2/Bax [21,26,28], mitochondria [38,44,45,49,51,57,63,64], oxidative stress [21,23,32,49,57,61,70], and endoplasmic reticulum stress [38].…”
Section: Introductionmentioning
confidence: 99%